Some lessons from Prophet Muhammad(SAW) in architecture: the Prophet's Mosque in Madinah - Omer, Spahic (IIUM Press, 2010)
This paper discusses some lessons in architecture that can be gleaned using the Prophet's Mosque in Madinah as a case study. The paper deals with the following main themes: the meaning and significance of Islamic architecture; function form relationship; respect for the environment; cleanliness; comprehensive excellence; promoting just social interactions; safety; and the relationship between the indigenous and foreign influences in the spheres of Islamic architecture. Every theme discussed signifies a permanent feature of Islamic architecture which derives its strength and merit from the Prophet's experiences. Hence, a close analogy is drawn in the paper between those architectural features and the Prophet.